Two new gurnards of the genus Pterygotrigla (Scorpaeniformes: Triglidae) from Australian seas - Last, Peter; Richards, William J. (Zootaxa, 2012)
In recent years there has been considerable research activity devoted to the triglid fauna of Australia, and included within this work has been an investigation of the genus Pterygotrigla. This fauna is considered to be amongst the most diverse of any region and multiple undescribed taxa occur in these seas. Two new species belonging to the subgenus Pterygotrigla are described from northern Australia. Pterygotrigla (Pterygotrigla) gomoni sp. nov. occurs in the eastern Indian Ocean on the upper continental slope off Western Australia, and P. (Pterygotrigla) saumarez sp. nov. occurs in the south-west Pacific on the outer continental shelf and upper slope off central and southern Queensland. These species differ markedly from each other in morphology, and are distinguished from other members of the subgenus by a combination of morphometrics, meristics, morphology of the head (in particular elements of its spination), shape and distribution of the dorsal-fin bucklers, and pectoral-fin coloration.